IMPROVING STUDENTS’ SPEAKING SKILL THROUGH VISUAL AIDS IN THE SECOND YEAR STUDENTS OF ENGLISH EDUCATION DEPARTMENT STATE ISLAMIC UNIVERSITY OF ALAUDDIN MAKASSAR - Muhammad Syahruddin Nawir; Multazam Abubakar; Meidaryanti (Univeristas Islam Negeri (UIN) Alauddin Makassar, 2022)
This research was an experimental research. This research aimed to find out the improvement of students’ speaking skills with a research objective; to find out the improvement of Students’ Speaking Skills by using visual aids in the Second Year Students of the English Education Department State Islamic University of Alauddin Makassar. The visual aids that the researcher used in this research were pictures and videos. This research was conducted at English Education Department State Islamic University of Alauddin Makassar the second-year students. In this research, the population was 101 students in the second year of EED. The sample was 50 students. There were 25 students in EED A as an experimental group and 25 students in EED B as a control group. The instrument that the researcher used in this research to collect data were speaking tests. The data were analyzed quantitatively using SPSS 23.0 version. The findings of the research showed that the use of visual aids was able to improve students’ speaking skill in the Second Year Students of English Education Department State Islamic University of Alauddin Makassar.